PENILAIAN TNF-ALFA PADA HATI MENCIT JANTAN SETELAH PEMBERIAN EKSTRAK ETANOL MANGGIS Garcinia mangostana L DENGAN METODE IMUNOHISTOKIMIA - Nora Maulina (Pascasarjana Universitas Negeri Medan, 2015)
Abstract Mangosteen peel extract is now widely used as an alternative treatment by society as an anti-oxidant without knowing the side effects. Consumption Monosodium glutamate (MSG) is used as a flavor enhancer in the food can cause various side effects due to formation of free radicals in the body such as liver dysfunction. The research method using true experimental designs aimed at comparing the effect of ethanol extract of mangosteen peel (EEKM) on liver damage caused by MSG administration to vitamin E. Of 15 fish samples DDW strain male mice, which were divided into three treatment groups, namely control group / distilled water (P0), MSG administration group (P2), group administration MSG and EEKM(P3). Then assessed liver function as well as evaluating the level of immunohistochemical staining of liver damage with TNF-α (NBP1-67 821, pAb, 1:50 dilution). Ethanol extract of mangosteen peel and are able to improve the look of immunohistochemical expression of TNF-α inflammatory process caused by MSG administration(p>0,05). Keywords: monosodium glutamate, ekstrak etanol kulit manggis, TNF-α.